2016
DOI: 10.2147/ott.s95985
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TMEM16A suppressed MAPK and inhibited cell proliferation and migration in hepatocellular carcinoma

Abstract: TMEM16A plays an important role in cell proliferation in various cancers. However, less was known about the expression and role of TMEM16A in hepatocellular carcinoma. We screened the expression of TMEM16A in patients’ hepatocellular carcinoma tissues, and also analyzed the biological function of hepatocellular carcinoma cells by knockdown of TMEM16A, as well as the expression of MAPK signaling proteins, including p38, p-p38, ERK1/2, p-ERK1/2, JNK, and p-JNK, and cell cycle regulatory protein cyclin D1 in TMEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…Before it was identified as a CaCC, TMEM16A had been found to be amplified in oral cancer, head and neck squamous cell carcinoma (HNSCC), gastrointestinal stromal tumor (GIST), breast cancer, and esophageal squamous cell (ESCC) cancer under other names such as FLJ10261, TAOS1 (tumor amplified and overexpressed sequence 1) and DOG1 (discovered on GISTs protein 1) [ 37 41 ]. Recently, TMEM16A has been reported to be highly expressed in many human tumors including breast cancer [ 42 , 43 ], HNSCC [ 44 47 ], colorectal cancer (CRC) [ 48 , 49 ], ESCC [ 50 ], lung cancer [ 51 ], hepatocellular carcinoma [ 52 ], prostate cancer [ 53 ], gastric cancer [ 54 , 55 ], and glioma [ 56 ] (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before it was identified as a CaCC, TMEM16A had been found to be amplified in oral cancer, head and neck squamous cell carcinoma (HNSCC), gastrointestinal stromal tumor (GIST), breast cancer, and esophageal squamous cell (ESCC) cancer under other names such as FLJ10261, TAOS1 (tumor amplified and overexpressed sequence 1) and DOG1 (discovered on GISTs protein 1) [ 37 41 ]. Recently, TMEM16A has been reported to be highly expressed in many human tumors including breast cancer [ 42 , 43 ], HNSCC [ 44 47 ], colorectal cancer (CRC) [ 48 , 49 ], ESCC [ 50 ], lung cancer [ 51 ], hepatocellular carcinoma [ 52 ], prostate cancer [ 53 ], gastric cancer [ 54 , 55 ], and glioma [ 56 ] (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…TMEM16A also activates the Ras-Raf-Mek-ERK1/2 signaling pathway in UM-SCC1 HNSCC cells and T24 bladder cells [ 44 ]. In SMMC-7721 human hepatoma cells, TMEM16A activates the p38 signaling pathway [ 52 ]. TMEM16A activates the NFκB signaling pathway and promotes the gene transcription in glioma cells [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that TMEM16A is closely related to the apoptosis of cancer (Wilkerson and Reis-Filho 2013), suggesting that TMEM16A may be a potential biomarker of some aggressive diseases (Deng et al 2016;Song et al 2018;Frobom et al 2019). For normal cells of the body, such as podocytes (Lian et al 2017) and smooth muscle cells Zeng et al 2019), overexpression of TMEM16A can promote apoptosis of these cells and further lead to the occurrence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and function of TMEM16A vary with cell type. Some studies have shown that TMEM16A can aggravate the disease by inhibiting apoptosis in cancer and tumors, suggesting that TMEM16A may be a potential biomarker of some aggressive diseases (Deng et al 2016;Song et al 2018;Frobom et al 2019). For normal cells of the body, such as podocytes (Lian et al 2017) and smooth muscle cells (Lian et al 2017), overexpression of TMEM16A can promote apoptosis of these cells and further lead to the occurrence of disease.…”
Section: Discussionmentioning
confidence: 99%